Targeting Education as a Barrier to Implement Hypofractionation: Results of a Country-Wide Training Program - María Caicedo-Martínez, MD; Benjamin Li, MD, MBA; Alejandro González-Motta, MD; Caroline Carlson, BA; Hong Zhu, BS; Iván Bobadilla, MD; David Martínez, MD (Advances in Radiation Oncology, 2023)
Introduction: Access to radiation therapy in low- and middle-income countries (LMICs) could be improved with modern hypofractionated radiation therapy schedules, although their adoption remains limited. We aimed to evaluate perceptions regarding hypofractionation and the effect of a dedicated curriculum in an LMIC. Methods and Materials: We developed a pilot e-learning hypofractionation curriculum focused on breast, prostate, rectal cancer, and high-grade glioma in Colombia. International educators taught 13 weekly, 90-minute sessions. Participants completed pre- and postcurriculum questionnaires regarding hypofractionation attitudes, 1 to 5 Likert-scale self-confidence, and practices for 12 clinical scenarios. Physicians’ responses were categorically scored “1” (for hypofractionation or ultrahypofractionation) or “0” (for conventional fractionation). We used the paired t test to measure pre- versus postcurriculum differences in self-confidence and the McNemar test to detect differences in hypofractionation selection. Results: Across 19 cities in Colombia, 147 clinicians enrolled: 61 radiation oncologists, 6 radiation oncology residents, 59 medical physicists, 18 physics residents, and 3 other staff. Among physicians, education was the greatest barrier to select hypofractionation, common in ultrahypofractionation for prostate (77.6%) and breast cancer (74.6%) and less common for moderate hypofractionation of prostate (61.2%) and breast cancer (52.2%). Additional perceived barriers included unfamiliarity with clinic protocols (7%-22%), clinical experience (5%-15%), personal preference (3%-16%), and lack of technology (3%-20%), with variation across different clinical settings. After the curriculum, paired (n = 38) physicians’ selection of hypofractionation increased across all disease sites (mean aggregate score 6.2/12 vs 8.2/12, P <.001). Self-confidence among paired clinicians (n = 87) increased for prostate ultrahypofractionation (+0.45), rectal ultrahypofractionation (+0.43), breast hypofractionation (+0.38), and prostate hypofractionation (+0.23) (P ≤ .03). Conclusions: In an LMIC with a bundled payment system, lack of education and training was a perceived barrier for implementation of hypofractionation and ultrahypofractionation. A targeted e-learning hypofractionation curriculum increased participant confidence and selection of hypofractionated schedules.